2013
DOI: 10.1021/ol402161j
|View full text |Cite
|
Sign up to set email alerts
|

Red-Hair-Inspired Chromogenic System Based on a Proton-Switched Dehydrogenative Free-Radical Coupling

Abstract: In the presence of micromolar peroxides or biometals (Fe(III), Cu(II), V(V) salts), and following a strong acid input, the stable 3-phenyl-2H-1,4-benzothiazine is efficiently converted to a green-blue Δ(2,2')-bi(2H-1,4-benzothiazine) chromophore via dehydrogenative coupling of a 1,4-benzothiazinyl radical. The new system is of potential practical interest for colorimetric peroxide and redox biometal detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…It has been suggested that the lower ionization potential of pheomelanin (i.e., the energy required to remove an electron from the molecule), favoring formation of sulfur‐stabilized radical cations, and the lower melanosomal pH of pheomelanin synthesis than eumelanin synthesis play some role in promoting ROS formation (Mitra et al., ). This suggestion, though chemically questionable due to the lack of specific evidence for sulfur‐stabilized radical cations in pheomelanins, would be consistent with the remarkable ability of the benzothiazines constituents of pheomelanins to undergo H‐atom abstraction and free‐radical dimerization upon protonation (Leone et al., ; Napolitano et al., ) (Figure ).…”
Section: The Dark Chemistry Of Pheomelanin: Prooxidant and Redox Propmentioning
confidence: 71%
“…It has been suggested that the lower ionization potential of pheomelanin (i.e., the energy required to remove an electron from the molecule), favoring formation of sulfur‐stabilized radical cations, and the lower melanosomal pH of pheomelanin synthesis than eumelanin synthesis play some role in promoting ROS formation (Mitra et al., ). This suggestion, though chemically questionable due to the lack of specific evidence for sulfur‐stabilized radical cations in pheomelanins, would be consistent with the remarkable ability of the benzothiazines constituents of pheomelanins to undergo H‐atom abstraction and free‐radical dimerization upon protonation (Leone et al., ; Napolitano et al., ) (Figure ).…”
Section: The Dark Chemistry Of Pheomelanin: Prooxidant and Redox Propmentioning
confidence: 71%
“…This position experiences the acid-activatable electron withdrawing effect of the imine moiety, sustaining either facile H-atom abstraction leading to captodatively stabilized free radical intermediates, [26,27] or condensation with various aldehyde derivatives to produce a range of cyanine-type chomophores. Noticeable applications of this chemistry include colorimetric peroxide and/or redox biometal detection, [26] pH sensing via reversible chromophoric changes that can be repeated over several cycles, [28] or the development of a modular dye platform for one-time-pad molecular cryptography. [29] The manifold synthetic opportunities offered by the BTZ system are schematically illustrated in Figure 2.…”
Section: The Dopaquinone-cysteine Route To Photochromic and Acidichromic Chromophoresmentioning
confidence: 99%
“…The trichocyanines, in particular, showed an extension of the conjugated system compared to that exhibited by Δ 2,2’ -bi-(2 H -1,4-benzothiazine) [ 32 , 34 ], which expectedly resulted in a larger bathochromic shift in acid. Therefore, variation of the π-bridge could be recognized as a facile and effective approach for developing push-pull chromophores with specific properties and easy tunability by modulating the electron-donating substituent(s) on the phenyl ring ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%